Design of a test suite for the jumpstart just-in-time signaling protocol - Zaim, A. Halim (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
We present a two step design of the just-in-time (JIT) signaling scheme running over a core dWDM network which utilizes optical burst switches (OBS). In the first step, we apply an eight-tuple extended finite state machine (EFSM) model to formally specify the protocol. Using the EFSM model, we define the communication between a source client node and a destination client node through an ingress and an intermediate switch. The communication between the EFSMs is handled through messages. In the second step, we generate unique input–output sequences. We work on on-the-fly unicast connection over a prototype testbed.
Optica Applicata, Vol. 35, 2005, nr 2, s. 333-345
Keywords: optyka; optical burst switching (OBS); just-in-time (JIT) signaling; optical communication